2013
DOI: 10.5430/afr.v2n4p34
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Beta in the 19th Century

Abstract: This paper uses completely new data to study the variations in beta when it deviates from the constancy assumption presumed by the market model. The concentration of the literature on beta is based on post 1926 data. This makes the 19 th century Brussels Stock Exchange (BSE) data a very good out-sample dataset to test beta variations. Various models proposed in the literature to capture the variations in beta were studied. Blume's correlation techniques reveal that beta is not stable at the individual stocks l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The beta coefficient reflects the sensitivity of a stock to market movements and is one of the parameters of time series regression. Beta is usually estimated using a standard market model, with the statistical model linking stock returns with the market index [26]. This study uses an estimation period of 210 days as the observation period for estimating beta values [27].…”
Section: Betamentioning
confidence: 99%
See 1 more Smart Citation
“…The beta coefficient reflects the sensitivity of a stock to market movements and is one of the parameters of time series regression. Beta is usually estimated using a standard market model, with the statistical model linking stock returns with the market index [26]. This study uses an estimation period of 210 days as the observation period for estimating beta values [27].…”
Section: Betamentioning
confidence: 99%
“…The regression coefficient or beta (β) can be calculated using the following regression equation: Beta estimated using the market model will be biased for an illiquid market; thus, for Indonesia, which has an illiquid market, one of the methods that can be used to correct the occurrence of bias is Dimson beta. This is calculated by summing the lead and lag coefficients in a multiple regression of market returns with the dependent variable as the time series return rate and the independent variables as the market return and the lead and lag variables on the market index [26].…”
Section: Betamentioning
confidence: 99%
“…Similar finding was observed by study of Matteev (2004), and Armitage & Brzeszczynski (2011) and they stressed that beta calculated in daily and weekly returns were more stable than that of monthly returns. In recent literature, Mensah (2013) observed that beta behavior had changed, and the infrequently traded shares were more volatile than the frequently traded share. Similarly, Oprea (2015) suggested that when return interval increased, the beta of infrequently traded shares increased and that of frequency would decrease even when standard market model was applied.…”
Section: Related Literaturementioning
confidence: 99%
“…The study of Mensah (2013) and Mensah (2015) both highlighted that portfolio beta decreased with the increase in portfolio size. Similarly, portfolio returns increased with the increase of portfolio size to the maximum of seven shares out of ten shares used.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation